The Interaction of Sec-O-Glucosylhamaudol With CYP3A4/CYP2D6 by Computer Simulation and Spectral Techniques - Yutong Du; Guiming Liu; Di Lian; Jingjing Cui; Yuan Li; Li Li (Journal of Spectroscopy)
CYP3A4 and CYP2D6 were the most important isoforms of CYP450. Some herbal components could interact with CYP3A4 and CYP2D6 to cause serious interactions between drug and herbs. Sec-O-glucosylhamaudol (SOG), a chromone isolated from Saposhnikovia divaricate, had been reported to have many biological activities. In this work, the binding model and dynamic structural changes were predicted by computer simulation. SOG could enter the active center of CYP3A4/CYP2D6 and interacted with two enzymes by means of hydrogen bonds, electrostatic force, and hydrophobic force. The stability of CYP3A4/CYP2D6 induced by SOG was monitored using molecular dynamics simulation. Furthermore, SOG caused static quenching of CYP3A4 and CYP2D6. At the same temperature, the binding constant Kb1 of CYP2D6-SOG was much higher than CYP3A4-SOG, which proved that SOG had greater binding force on CYP2D6. The binding forces of CYP3A4/CYP2D6 with SOG obtained by fluorescence analysis were consistent with docking analysis based on negative ΔH and positive ΔS. Meanwhile, it was also proved that SOG had a remarkable impact on the secondary structure change of these two proteins through hydrophobic interaction, hydrogen bond, and electrostatic force.